Cultural Change of Mathematics Teachers' Views on Technology: Navigating the Artificial Intelligence Revolution - Utami, Niken Wahyu; Sagita, Laela; Rahmawati, Rina Dyah; Nurdianto, Heri (Universitas Dharma Wacana, 2024)
The development of technology related to Artificial Intelligence is growing rapidly, and one of its implications is the teaching of mathematics in the classroom. Therefore, it is necessary to conduct research on the perspective of mathematics teachers in addressing the development of artificial intelligence (AI) used in mathematics learning. This study examines the role of AI technology in facilitating pedagogical reform in mathematics education from the perspective of teachers. Through a questionnaire distributed to mathematics teachers, this paper identifies teachers' perspectives on the development of AI and its use in their classrooms. A total of 56 mathematics teachers participated in this study. In addition to the five-item questionnaire, an open-ended questionnaire was also provided. A number of AI that teachers use in their teaching are also mentioned in this paper. The paper also discusses the challenges that mathematics teachers face when using AI in mathematics lesson planning in their classrooms. It concludes that mathematics learning using AI has significant potential to improve students' competencies by equipping them with essential skills for the digital age